Short communication. Goat preferences for native woody shrubs in the Chaco Arido region of Cordoba, Argentina - Cora, A.=700 1 Nai Bregaglio, M.; Coirini, R.O.
(Es, En)
ilus., 19 ref.
Keywords: CABRA; NUTRICION ANIMAL; ARBUSTOS; PLANTAS LEÑOSAS; ZONA ARIDA; ARGENTINA